P113: The protective effect of G1958A SNP on the MTHFD1 gene in susceptibility to non-Hodgkin malignant lymphomas. Issue 1 (November 2015) - Berezina, O.; Shadrina, A.; Voropaeva, E.; Pospelova, T.; Filipenko, M.
Abstract : Background: Methylation systems in the cells play an important role in the metabolic processes such as purine nucleotide biosynthesis and gene and protein activity regulation. An imbalance between entities in folic acid metabolism can adversely affect nucleotide synthesis and the DNA repair and methylation system, which can cause genome instability and impairments in chromosome segregation, and lead to abnormal expression of proto-oncogenes and inactivation of tumor suppressor genes. These processes may underlie the development of a range of cancer disease, including Non-Hodgkin's lymphomas (NHL). Quite a few studies investigating the association of SNPs in the folate-metabolizing genes with NHL risk in populations of different ethnic origin are available to date. Because the low prevalence of this disease makes sampling difficult, most of these studies have small sizes, which may be one of the reasons why results obtained are often conflicting. The aim of this study was to investigate the role of some SNPs in folate genes (the C677T and A1298C SNPs in the MTHFR gene, A2756G in MTR, A66G in SHMT1, G1958A in MTHFD1 and 844ins68 in CBS) in genetic susceptibility to non-Hodgkin's malignant lymphoma in the west-Siberian region. Methods: 146 unrelated patients from the Haematological Center (Novosibirsk city) with various types of NHL were investigated. Genomic DNA was isolated from leukocytes in venous blood and from buccal epithelium, using the standard methods of DNA separation. A PCR-restriction fragment length polymorphism (RFLP) assay was used to detect the MTHFD1 G1958A and CBS 844ins68 SNPs. Genotyping of the MTHFR, MTR, MTRR and SHMT1 gene SNPs was carried out by real-time PCR allelic discrimination with TaqMan probes. The alleles and genotypes distribution of SNPs in patients were compared with their distribution in healthy white Russian subjects from Novosibirsk. Results: We determined the allele and genotype frequencies for seven SNPs in folate metabolism in NHL and control groups. For all these SNPs, the genotype frequencies were in Hardy–Weinberg equilibrium in the control group. There were no statistically significant differences in the frequencies of alleles and genotypes of polymorphic loci of MTHFR, MTRR, CBS, SHMT1 genes between patients with NHL and controls. However, theG1958A MTHFD1 polymorphism showed a significant association with aggressive NHL. The 1958A allele (OR = 0.578, C.I. [0.415–0.805], p  < 0.001) and AA MTHFD1 genotype (OR = 0.283, C.I. [0.130–0.613], p  < 0.0008) were associated with decreased risk of aggressive lymphoma. The association between folate genes and indolent non-Hodgkin's lymphoma was not revealed. The SNP G1958A causes the Arg653Gln substitution occurring in the formyltetrahydrofolate domain of the MTHFD enzyme. The substrate for this enzyme is tetrahydrofolate (THF). Potentially, the accumulation of THF results in an increase in 5, 10-methylenetetrahydrofolate concentration, which in turn may enhance the efficiency of thymidylate synthesis and DNA methylation. Together, these processes may contribute to inhibition of malignant transformation. Conclusion: G1958A SNP in the MTHFD1 gene contributes to susceptibility to NHL. The mutant allele and genotype determine the protective effect, probably, by affecting the concentration of intracellular folic acid metabolites.